POTENSI BAHAYA ERGONOMI PADA PEKERJA HOME INDUSTRY KUN ART DI JALAN DANAU SINGKARAK MEDAN TAHUN 2013 - Nadya .; eka Lestari; Muhammad Makmur Sinaga (Lingkungan dan Kesehatan Kerja, 2013)
Ergonomic Potensial Hazard in Home Industry Kun Art Workers at Jalan Danau Singkarak Medan 2013. One of the potential hazards at home industry which is still very less attention is the ergonomics potential hazards, this is caused by a lack of knowledge on the workers. The purpose of this research is to know at the ergonomic potential hazards at work process that focuses on human-machine systems, work posture, work station layout and manual handling. This is a descriptive research, by observing work activities starting from the process of pattern making, pattern assembly, attachment of finishing materials and processes contained at